Correlating polymer structure, dynamics, and function with atomic force microscopy. Issue 7 (23rd June 2021) - Murphy, Julia G.; Raybin, Jonathan G.; Sibener, Steven J.
Abstract: Since its development, atomic force microscopy (AFM) has become an indispensable tool for investigating fundamental and technological applications of polymer materials. The versatility of AFM imaging modes and operating conditions allows for nanoscale characterization of a range of dynamic processes, such as crystallization, phase separation, self assembly, and electronic transport. Advances in AFM technology, particularly high‐speed and high‐resolution imaging, enable investigation of polymer structure, function, and dynamics in real world conditions and across a range of relevant spatial and temporal scales. In this perspective, we highlight a collection of recent polymer studies that utilize AFM to correlate the function and structure of polymer films, with focus on its multiparametric imaging capabilities. As the complexity of polymer materials and morphologies continues to increase, AFM is well poised to meet the accompanying demand for nanoscale imaging and characterization. Abstract :